(3CHOGd GdCOhjIs - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG Gdbhd ai GdEHOGd HMSH eG QCi LRA ef CLRGA GdWH GdYXGe s
(3BNQgG (B:s
(3YGaJ HOdg ai GdfaY ef GdMei GdMGOI fUa hRfg CSGQhf hfUa hRfg CaSfJjfi s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1538) s
Keywords: (3GdWHs